Ambient particulate pollution and the world-wide prevalence of asthma, rhinoconjunctivitis and eczema in children: Phase One of the International Study of Asthma and Allergies in Childhood (ISAAC). Issue 5 (9th October 2009) - Anderson, H Ross; Ruggles, Ruth; Pandey, Kiran D; Kapetanakis, Venediktos; Brunekreef, Bert; Lai, Christopher K W; Strachan, David P; Weiland, Stephan K; ,
Abstract : Objectives: To investigate the effect of ambient particulate matter on variation in childhood prevalence of asthma, rhinoconjunctivitis and eczema. Methods: Prevalences of asthma, rhinoconjunctivitis and eczema obtained in Phase One of the International Study of Asthma and Allergies in Childhood (ISAAC) were matched with city-level estimates of residential PM10 obtained from a World Bank model. Associations were investigated using binomial regression adjusting for GNP per capita and for clustering within country. For countries with more than one centre, a two stage meta-analysis was carried out. The results were compared with a meta-analysis of published multi-centre studies. Results: Annual concentrations of PM10 at city level were obtained for 105 ISAAC centres in 51 countries. After controlling for GNP per capita, there was a weak negative association between PM10 and various outcomes. For severe wheeze in 13–14-year-olds, the OR for a 10 μg/m 3 increase in PM10 was 0.92 (95% CI 0.84 to 1.00). In 24 countries with more than one centre, most summary estimates for within-country associations were weakly positive. For severe wheeze in 13–14-year-olds, the summary OR for a 10 μg/m 3 increase in PM10 was 1.01 (0.92 to 1.10). This result was close to a summary OR of 0.99 (0.91 to 1.06) obtained from published multi-centre studies. Conclusions: Modelled estimates of particulate matter at city level are imprecise and incomplete estimates of personal exposure to ambient air pollutants. Nevertheless, our results together with those of previous multi-centre studies, suggest that urban background PM10 has little or no association with the prevalence of childhood asthma, rhinoconjunctivitis or eczema either within or between countries.